2017
DOI: 10.1063/1.5003908
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced vibrational solvatochromism and spectral diffusion by electron rich substituents on small molecule silanes

Abstract: Fourier transform infrared and two-dimensional IR (2D-IR) spectroscopies were applied to two different silanes in three different solvents. The selected solutes exhibit different degrees of vibrational solvatochromism for the Si-H vibration. Density functional theory calculations confirm that this difference in sensitivity is the result of higher mode polarization with more electron withdrawing ligands. This mode sensitivity also affects the extent of spectral diffusion experienced by the silane vibration, off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 85 publications
(120 reference statements)
4
14
0
Order By: Relevance
“…Recent work from our group has shown that the solvatochromic effect for the silicon hydride can be explained by a vibrational Stark effect with the addition of specific solvent−solute interactions in the case of hydrogen and halogen bond donors. 64 The FTIR peak widths in Figure 1a are slightly more sensitive to the different solvent environments, increasing in the order of none (green) < pentane (blue) < 2-propanol (black) < chloroform (red) and consistent with our previous report (excluding the solvent-free sample). 64 For comparison, Figure 1b shows the FTIR spectra of the oligomeric cross-linking species in the same solvents prior to being polymerized into the PDMS elastomer.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Recent work from our group has shown that the solvatochromic effect for the silicon hydride can be explained by a vibrational Stark effect with the addition of specific solvent−solute interactions in the case of hydrogen and halogen bond donors. 64 The FTIR peak widths in Figure 1a are slightly more sensitive to the different solvent environments, increasing in the order of none (green) < pentane (blue) < 2-propanol (black) < chloroform (red) and consistent with our previous report (excluding the solvent-free sample). 64 For comparison, Figure 1b shows the FTIR spectra of the oligomeric cross-linking species in the same solvents prior to being polymerized into the PDMS elastomer.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…64 The FTIR peak widths in Figure 1a are slightly more sensitive to the different solvent environments, increasing in the order of none (green) < pentane (blue) < 2-propanol (black) < chloroform (red) and consistent with our previous report (excluding the solvent-free sample). 64 For comparison, Figure 1b shows the FTIR spectra of the oligomeric cross-linking species in the same solvents prior to being polymerized into the PDMS elastomer. The hydride on the cross-linking oligomer is only slightly more solvatochromic with its frequency shifts spanning a range of 4 cm −1 and has the same trend except for a higher frequency in pentane than without solvent.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
See 3 more Smart Citations